2021
DOI: 10.1002/cncy.22531
|View full text |Cite
|
Sign up to set email alerts
|

Serial FNA allows direct sampling of malignant and infiltrating immune cells in patients with B‐cell lymphoma receiving immunotherapy

Abstract: BACKGROUND: Fine-needle aspiration (FNA) is used to diagnose malignancies, recurrences, and metastases. The procedure is quick and well tolerated and can be facilitated by ultrasound guidance. METHODS: This article describes the authors' experience in using serial FNA to harvest cellular material during 4 clinical trials of immunotherapy by in situ vaccination in patients with low-grade lymphoma. RESULTS: Two hundred ninety-six FNA samples were collected from 44 patients over a span of approximately 6 weeks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Our cell viability ranged from 58% to 76%, and other reports describe a wide range from 30% to 90%. 5,12,21 Technique B had the highest total number of live cells and the second highest percentage viability. It was the only technique with a vacuum and air forced through the needle to expel the contents into media prior to flushing the needle with media.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our cell viability ranged from 58% to 76%, and other reports describe a wide range from 30% to 90%. 5,12,21 Technique B had the highest total number of live cells and the second highest percentage viability. It was the only technique with a vacuum and air forced through the needle to expel the contents into media prior to flushing the needle with media.…”
Section: Discussionmentioning
confidence: 97%
“…FNA of the lymph nodes allows for longitudinal analysis of different cell subsets and, in some cases, lymphoid viral load with increased frequency. [5][6][7][8][9][11][12][13][14][15][16] It has also been efficacy, less invasive sampling techniques are essential. 8,11 Previous publications have demonstrated that the percentages of particular T lymphocytes correlated significantly or strongly, depending on the cell subset, between lymph node FNA and lymph node excisional biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations